Adherence to American Association for the Study of Liver Diseases guidelines for the management of hepatocellular carcinoma: results of an Italian field practice multicenter study. (February 2013) - Borzio, Mauro; Fornari, Fabio; De Sio, Ilario; Andriulli, Angelo; Terracciano, Fulvia; Parisi, Giancarlo; Francica, Gianpiero; Salvagnini, Mario; Marignani, Massimo; Salmi, Andrea; Farinati, Fabio; Carella, Alessandra; et al.
Aim: Adherence to and the applicability of practice guidelines for the management of hepatocellular carcinoma (HCC) in field practice have not been fully addressed. We designed a multicenter field practice prospective study to evaluate the adherence to the 2005 American Association for the Study of Liver Diseases guidelines in Italy.Materials & methods: The study began in September 2008 and consecutively enrolled cirrhotic patients with newly diagnosed HCC from 30 local, nonreference centers in Italy. Patients were stratified according to Child–Pugh, the model for end-stage liver disease, tumor-node metastasis, performance status and the Barcelona Clinic Liver Cancer (BCLC) classifications. The diagnostic and therapeutic strategies adopted in each individual patient were recorded. Statistical analysis was carried out on 536 patients using all of the valuable data.Results: A total of 286 (54.5%) patients were ≥70 years old. Comorbidities, recorded in 397 (74%) patients, were classified as moderate to severe in 170 patients (43%). Overall, 174 (59%) patients with early-stage BCLC were ≥70 years; 104 (35%) of these had moderate-to-severe comorbidities and 54% were under a regular US surveillance program. Diagnosis was performed by computed tomography in 93% of patients, contrast-enhanced ultrasound in 62% and MRI in 17%. In patients with nodules of ≤2 cm, adherence to noninvasive diagnostic criteria was 56%. Adherence to the BCLC classification was shown to be suboptimal overall, particularly regarding allocation to surgical procedures, and a total of 119 patients (40%) with BCLC stage A did not receive curative therapies.Conclusions: This multicenter survey showed that, in the 'real world', adherence to the both the diagnostic and therapeutic American Association for the Study of Liver Diseases 2005 algorithms was low, particularly in patients with early-stage HCC. Difficulties in applying the algorithms in routine clinical practice and the high prevalence of older patients with relevant comorbidities may account for our findings. Strategies to help improve adherence to international guidelines for HCC in field practice are required.